POLYMORPHIC PROFILES OF Ganoderma spp. ISOLATES FROM BANYUMAS, CENTRAL JAVA, INDONESIA - Nuniek Ina Ratnaningtyas; Agus Hery Susanto; Ana Yulia (BIOTROPIA, 2019)
Ganoderma spp. are known as both beneficial and harmful fungi to humans. These are distributed worldwide in sufficiently high diversity. To generate a polymorphic profile and a genetic inter-relationship of several isolates of Ganoderma spp., a study was conducted using the Random Amplified Polymorphic DNA (RAPD) markers on Ganoderma spp. from Banyumas Regency, Central Java, Indonesia. The fruiting bodies of the collected Ganoderma spp. were first morphologically characterized, then analyzed using RAPD with four random primers, i.e., OPC-1, OPC-2, OPC-4, and OPC-5. The results revealed that the four primers generated polymorphic bands of the 10 samples with a polymorphism level of 100%, showing high genetic diversity. The level of genetic similarity ranged between 0.48 and 0.82, indicating moderate similarities among samples. The constructed dendrogram resulted in the grouping of the Ganoderma spp. isolates into three clusters at a similarity coefficient of 0.63, but neither according to geographical locations nor growth substrates.